Eastern North America materials, Frank G. Speck Papers - Speck, Frank G. (Frank Gouldsmith), 1881-1950; Hardenbrook, Louise; Greywacz, Kathryn B.; Howells, W. W. (William White), 1908-2005; Launer, Philip; Rathbone, Perry Townsend, 1911-2000; Fewkes, Vladimir J.; Hawkes, Ernest William, 1883-; Johnson, Frederick, 1904-1994; McKern, W. C. (Will Carleton), 1892-; Ritchie, William A. (William Augustus), 1903-1995; Spaulding, Albert C. (Albert Clanton), 1914-1990; et al. (1915)
This entry concerns materials relating to Speck's general study of Native American peoples, languages, and cultures east of the Mississippi, as well as to his activities as a consulted expert in the field. Includes Speck's miscellaneous notes on the southeast; notes on "tribal remnants" in the southeast; notes on shamanism in the northeast; notes on the 1941 symposium Man in Northeastern America; offprints, drafts, and synopses of the work of others, sometimes with Speck's notes, including several that were printed in Frederick Johnson's 1946 volume based on the symposium, Man in Northeastern North America; archaeological reports on southeastern pottery, mound sites, and the Georgia coast; a student's master's thesis on mound-builders; and letters from various correspondents regarding eastern Indian baskets, museum specimens, the sale of Indian art and specimens, the ethnohistory of the southeast, Indian place names, archaeological sites in Pennsylvania and Massachusetts, scapulimancy, copies of Indian treaties from a museum in Nova Scotia, and other topics.